2020
DOI: 10.1101/2020.04.25.060665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic inactivation of the translin/trax microRNA-degrading enzyme phenocopies the robust adiposity induced byTranslin(Tsn) deletion

Abstract: Objective: Deletion of Translin (Tsn) from mice induces an unusual metabolic profile characterized by robust adiposity, normal body weight and glucose tolerance.Translin (TN) protein and its partner, trax (TX), form the TN/TX microRNA-degrading enzyme. Since the microRNA system plays a prominent role in regulating metabolism, we reasoned that the metabolic profile displayed by Tsn KO mice might reflect dysregulation of microRNA signaling. Methods:To test this hypothesis, we inserted a mutation, E126A, in Tsnax… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Mice with floxed alleles of Tsn or Tsnax were generated on a C57BL/6J background using CRISPR/Cas9 technology as described in Fu et al [25]. The following Cre driver or reporter lines were obtained from JAX labs or MMRRC (Drd1-Cre (EY217); Ai9 #007909; DAT-Cre #006660; Adora2a-Cre #036158; Ubiquitin C-CreERT2 #007001).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with floxed alleles of Tsn or Tsnax were generated on a C57BL/6J background using CRISPR/Cas9 technology as described in Fu et al [25]. The following Cre driver or reporter lines were obtained from JAX labs or MMRRC (Drd1-Cre (EY217); Ai9 #007909; DAT-Cre #006660; Adora2a-Cre #036158; Ubiquitin C-CreERT2 #007001).…”
Section: Animalsmentioning
confidence: 99%
“…In recent studies, we have found that global, conditional deletion of Tsn in adulthood, using tamoxifen-induced activation of the UBC-CreERT2 allele, does not produce increased adiposity [25]. Therefore, we used this manipulation to examine the effect of Tsn deletion on the locomotor response to amphetamine in the absence of increased adiposity.…”
Section: Global Conditional Deletion Of Tsn In Adulthood Does Not Almentioning
confidence: 99%